Giant suppression of shot noise in double barrier resonant diode: a signature of coherent transport - Aleshkin, V. Ya (2003)
Shot noise suppression in double barrier resonant tunnelling diodes with a Fano factor well below the value of 0.5 is theoretically predicted. This giant suppression is found to be a signature of coherent transport regime and can occur at zero temperature as a consequence of the Pauli principle or at sufficiently high temperatures above 77 K as a consequence of a long-range Coulomb interaction. These predictions are in agreement with experimental data.